Enhancing Quality Appointment, Preparation and Support System for Malaysian Principals - Husaina Banu Kenayathulla; Muhammad Faizal A. Ghani; Norfariza Mohd Radzi (MDPI AG, 2024)
Educational leaders in the 21st century are under increasing pressure since they need to consistently upskill and reskill themselves so that they can adapt to rapid changes and be prepared to improve the quality of future education, as well as meet the demands of diverse stakeholders. Previous studies in the Malaysian context mostly focused on leadership training for newly appointed school principals, but there has not been much emphasis on continuous professional development for school leaders. This article provides an in-depth analysis of the appointment, preparation, and support system for Malaysian principals. In this study, a qualitative methodology has been applied, which involves document analysis based on policy documents, media, and previously published journal articles. The findings suggest that internal and external supports are currently being provided to principals. However, it proposes a wider framework of support for principals comprising internal and external support, including smart partnerships with diverse stakeholders such as industries, non-profit organizations, and international counterparts. The results provide insights to policymakers on the importance of consistently supporting school leaders to upskill with multifaceted skills to perform multiple functions, such as technological, economic, social, cultural, political, and learning leadership.